Note on the Effect of Frequent Freshenings on Resin Yield from Chil (Pinus roxburghii) - Singh, R. V.; Sharma, K. C. (Indian Forester, 1974)
Results of an experiment conducted to study the effect of three frequencies of freshening on resin yield from blazes paired on individual tree are summarized. Three freshenings a week increased resin yield significantly over two freshenings a week which in turn gave significantly higher resin yield than one freshening a week. Resin yield per blaze per freshening decreased with increased frequency of freshening.